İlerleme aşamasındaki öğr. için çello repertuvarı - Dikener, Şölen (Ankara: Müzik Eğitimi Yayınları, 2023)
E- BOOK - A Collection of Essential Repertory for the Advancing Cellist (wihh piano acc.) / Şölen Dikener / E- Kitap - İlerleme Aşamasındaki Öğrenciler için Çello Repertuvarı (Piyano Eşlikli) / Şölen Dikener / Index - İçindekiler / S H O R T P I E C E S / Hugo BECKER First Sight in D major, Op.7, No. / Luigi BOCCHERINI Allegretto in C major from Sonata G.6 / Karl DAVIDOFF Romance without Words in G Major, Op.23 / Jean Pierre DUPORT Adagio in A minor from Sonata Op.2, No.4 / Auguste FRANCHOMME Meditation in D Major, Op.41 / Georg GOLTERMANN Nocturne in D Minor, Op.43, No.3 / Georg GOLTERMANN Romance in C Major from Sonatina, Op.114 / Anton KRAFT Cossacks' Rondo in C Major from Concerto, Op.4 / Alfredo PIATTI Adagio in C Major from Concertino, Op. 18 / David POPPER Tarantella in G Major, Op.33 / David POPPER Once Upon More Beautiful Days in A Minor, Op.64, No.1 / François SERVAIS La Romanesca in B Minor / William Henry SQUIRE Humoresque in F Major, Op.26 / William Henry SQUIRE At Twilight in C Major, Op.16, No.1 / Heitor VILLA-LOBOS Song of the Black Swan / S O N A T A S / Jean BARRIÈRE Sonata in E minor, Book One, No.1 / Jean Baptiste BRÉVAL Sonata in C Major, Op.40, No.1 / Jean Baptiste BRÉVAL Sonata in F Major, Op.40, No.2 / Jean Baptiste BRÉVAL Sonata in G Major, Op.40, No.3 / James CERVETTO Sonata in D majör / Giovanni Battista CIRRI Sonata in C Major, Op.15, No.2 / Julius KLENGEL Sonatina in C Major, Op.47, No.1 / Bernhard ROMBERG Sonata in E minor, Op.38, No.1 / C O N T E R T O S / Friedrich SEITZ Concerto No.2 in C major, Op.13 / Friedrich SEITZ Concerto No.5 in D major, Op.22 / D U O S / Jean Baptiste BRÉVAL Duo Sonata in F major, No.6 / Friedrich DOTZAUER Duo Sonata in G major, Op.103, No.1 / Carlo GRAZIANI Duo Sonata in G major, Op.2, No.5 / Pierre HUS-DESFORGES Duo Sonatina in G Major, No.1 / Friedrich KUMMER Duo in C major, Op.22, No.1 / Friedrich KUMMER Siciliano in G Major, Op.33 / Salvatore LANZETTI Duo Sonata in G Major, No.1 / Sebastian LEE Andante Cantabile in A Minor, Op.36, No.2 / Sebastian LEE Duo in F Major, No.1 / Jacques OFFENBACH Duo in G major, Op.50, No.1
2
Keywords: Viyolonsel